Central nervous system abnormalities in patients with PMP22 gene mutations: a prospective study. Issue 4 (15th December 2012) - Chanson, Jean-Baptiste; Echaniz-Laguna, Andoni; Blanc, Frédéric; Lacour, Arnaud; Ballonzoli, Laurent; Kremer, Stéphane; Namer, Izzie-Jacques; Lannes, Béatrice; Tranchant, Christine; Vermersch, Patrick; de Seze, Jérôme
Abstract : Background: Mutations of the peripheral myelin protein-22 ( PMP22 ) gene are the most common cause of inherited disease of the peripheral nervous system (PNS), with its deletion resulting in hereditary neuropathy with liability to pressure palsies (HNPP), and its duplication inducing Charcot–Marie–Tooth 1A (CMT1A) disease. Although mainly expressed in the PNS, PMP22 mRNA and protein are also present in the central nervous system (CNS). Objective: To investigate whether patients with PMP22 mutations present with CNS abnormalities. Methods: Fifteen patients with HNPP and 15 patients with CMT1A disease were prospectively included and their brain MRI and neuropsychological assessment were compared with those of healthy subjects. We evaluated, in particular, the volumes of grey and white matter (GM and WM) and looked for metabolic changes using spectroscopy, and abnormal architecture using fractional anisotropy (FA) measurement. A post mortem examination of the CNS of a patient with PMP22 gene duplication was also performed. Results: We found a decrease in the volume of WM in 70% of patients, a reduced creatine level in WM in 28% and a cognitive impairment in 70%. FA was significantly altered in several areas of WM, including the columns of the fornix. The results for WM volume, creatine level in WM and cognitive testing showed that 47% of patients (patients with HNPP and those with CMT1A) presented with at least two abnormal results. Pathological examination of the brain of a patient with PMP22 gene duplication showed diffuse hypomyelination sparing the U fibres. Conclusions: This study demonstrates that altered PMP22 gene expression induces significant CNS alterations in patients with HNPP and CMT1A, including cerebral WM abnormalities and cognitive impairment.